The role of primary tumor resection in colorectal cancer patients with asymptomatic, synchronous unresectable metastasis: Study protocol for a randomized controlled trial. Issue 1 (December 2016) - Kim, Chang; Baek, Jeong-Heum; Choi, Gyu-Seog; Yu, Chang; Kang, Sung; Park, Won; Lee, Bong; Kim, Hyeong; Oh, Jae; Kim, Jae-Hwang; Jeong, Seung-Yong; Ahn, Jung; et al.
Abstract Background Approximately 20 % of all patients with colorectal cancer are diagnosed as having Stage IV cancer; 80 % of these present with unresectable metastatic lesions. It is controversial whether chemotherapy with or without primary tumor resection (PTR) is effective for the treatment of patients with colorectal cancer with unresectable metastasis. Primary tumor resection could prevent tumor-related complications such as intestinal obstruction, perforation, bleeding, or fistula. Moreover, it may be associated with an increase in overall survival. However, surgery delays the use of systemic chemotherapy and affects the systemic spread of malignancy. Methods/design Patients with colon and upper rectal cancer patients with asymptomatic, synchronous, unresectable metastasis will be included after screening. They will be randomized and assigned to receive chemotherapy with or without PTR. The primary endpoint measure is 2-year overall survival rate and the secondary endpoint measures are primary tumor-related complications, quality of life, surgery-related morbidity and mortality, interventions with curative intent, chemotherapy-related toxicity, and total cost until death or study closing day. The authors hypothesize that the group receiving PTR following chemotherapy would show a 10 % improvement in 2-year overall survival, compared with the group receiving chemotherapy alone. The accrual period is 3 years and the follow-up period is 2 years. Based on the inequality design, a two-sided log-rank test with α-error of 0.05 and a power of 80 % was conducted. Allowing for a drop-out rate of 10 %, 480 patients (240 per group) will need to be recruited. Patients will be followed up at every 3 months for 3 years and then every 6 months for 2 years after the last patient has been randomized. Discussion This randomized controlled trial aims to investigate whether PTR with chemotherapy shows better overall survival than chemotherapy alone for patients with asymptomatic, synchronous unresectable metastasis. This trial is expected to provide evidence so support clear treatment guidelines for patients with colorectal cancer with asymptomatic, synchronous unresectable metastasis. Trial registration Clinicaltrials.govNCT01978249 .